2013
DOI: 10.1186/1471-2377-13-116
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of prognosis for newly diagnosed epilepsy in east China

Abstract: BackgroundLimited data are available on the outcome of antiepileptic drug treatment response in patients of Chinese Han ethnicity with newly diagnosed epilepsy. We sought to explore the prognosis with antiepileptic drug treatment and to identify the predictors of poor drug control of seizures in these patients.MethodsFor at least 2 years, we prospectively followed up a cohort of patients with newly diagnosed epilepsy and analyzed the response to each antiepileptic drug. Cumulative risk for seizure relapse afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
(41 reference statements)
5
26
5
Order By: Relevance
“…The probability of retaining the first drug in the treatment schedule and starting a period of remission lasting until the end of follow‐up, or of stopping the first treatment for terminal remission, was high, 48% at 20 years. Others found that the proportion of seizure‐free individuals on the first AED ranged from 5.4% to 62%; 63% of our patients never withdrew the first AED, and 51% of them started a period of remission lasting until the end of follow‐up. This finding supports the concept that in clinical practice the majority of people with epilepsy can be easily controlled with any of the available compounds even after long follow‐up periods.…”
Section: Discussionmentioning
confidence: 67%
“…The probability of retaining the first drug in the treatment schedule and starting a period of remission lasting until the end of follow‐up, or of stopping the first treatment for terminal remission, was high, 48% at 20 years. Others found that the proportion of seizure‐free individuals on the first AED ranged from 5.4% to 62%; 63% of our patients never withdrew the first AED, and 51% of them started a period of remission lasting until the end of follow‐up. This finding supports the concept that in clinical practice the majority of people with epilepsy can be easily controlled with any of the available compounds even after long follow‐up periods.…”
Section: Discussionmentioning
confidence: 67%
“…The studies were conducted between 1961 and 2012, and most studies (68.5%, n = 24) were published before the ILAE guidelines were available in 2010. There were only 4 studies with part of the study period after 2010 . Most (57.1%, n = 20) were cohort studies, 60.0% (n = 21) only included children (<17 years), and 17.1% (n = 6) and 37.1% (n = 13) were conducted in the United States and Europe, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that studies used different definitions of DRE because almost all of the studies included in the review were conducted before the publication of the ILAE guidelines. Only 4 studies recruited patients after the guidelines were published in 2010, and 2 implemented the ILAE definition prospectively . Although it has been reported consistently in the literature that an estimated 30%‐40% of patients with epilepsy will develop DRE, this review has found that few studies have used the ILAE definition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an Italian study performed by Gasparini indicated only 23% patients with newly diagnosed cryptogenic focal epilepsy attained seizure remission during follow-up, as the remission was defined as the absence of any seizure for at least five years [13]. In a Chinese cohort of 180 patients [14], Zhang et al found early remission was reached in 69.4% newly diagnosed patients, and 10.6% entered late remission whereas 20% patients failed to achieve remission. The higher remission rate could also be explained by the different definition, because in their study early remission was defined as one-year seizure free within the first year of treatment initiation, as opposed to late remission, which was defined after more than first year of treatment.…”
Section: Discussionmentioning
confidence: 98%